The Struggle of Seaking Happiness on me Before You Movie - Agatha Tresha Paranginangin; Desri Maria Sumbayak; Fikry Prastya Syaputra (MultiTech Publisher, 2024)
Happiness among people has been something quite familiar but unshaped, it has been difficult for people to feel happy in this era and many has started to wonder what is the real happiness. Do we need to feel the happiness in order to fell alive. This study explores the happiness in human live that consider to be important. This research undertakes the live of a character from a literary art that symbolize the authentic happiness itself. The findings indicate that characterization allow us to observe a character stages of emotions and feelings. findings also showed the three stages of happiness are the major evidence of experiencing True happiness itself and does it do. Findings showed that the happiness played a key role to help people condition and gave them the quality of living. However, research is limited to view extent considering the time allowance for the study, as well as the financial constraints experienced by the researcher. It is recommended to implement the three stages of happiness to give better Quality of living in human life.